2017
DOI: 10.1038/s41598-017-07108-9
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Supplementation Improves Maternal High Fat Diet-Induced Programming of Metabolic Dysfunction in Adult Male Rat Offspring

Abstract: The developmental origins of health and disease hypothesis proposes that an adverse early life environment, including in utero exposure to a maternal obesogenic environment, can lead to an increased long-term risk of obesity and related metabolic complications in offspring. We assessed whether maternal supplementation with conjugated linoleic acid (CLA) could prevent some of these adverse effects in offspring exposed to a maternal high fat diet. Sprague-Dawley dams consumed either a: control (CD), control with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Thus, there could be other possible mechanisms mediated by CLA that would be involved in the reduction in EWAT, such as the inhibition of SCD-1 activity, enhanced apoptosis of pre-adipocytes and adipocytes and/or lipolysis modulation (45) . In line with some of our results, it has been demonstrated that maternal c9,t11-CLA supplementation reversed HF diet-induced increases in fat mass, hyperleptinaemia and dyslipidaemia (20) , impaired insulin sensitivity and adipocyte hypertrophy (21) , and skeletal muscle atrophy and inflammation (51) in adult male rat offspring. However, there is no clear explanation of the mechanisms involved in the reduction in adipose tissue by c9,t11-CLA.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, there could be other possible mechanisms mediated by CLA that would be involved in the reduction in EWAT, such as the inhibition of SCD-1 activity, enhanced apoptosis of pre-adipocytes and adipocytes and/or lipolysis modulation (45) . In line with some of our results, it has been demonstrated that maternal c9,t11-CLA supplementation reversed HF diet-induced increases in fat mass, hyperleptinaemia and dyslipidaemia (20) , impaired insulin sensitivity and adipocyte hypertrophy (21) , and skeletal muscle atrophy and inflammation (51) in adult male rat offspring. However, there is no clear explanation of the mechanisms involved in the reduction in adipose tissue by c9,t11-CLA.…”
Section: Discussionsupporting
confidence: 91%
“…Although earlier studies have investigated the influence of CLA incorporated into maternal diet on the various metabolic dysfunctions in their offspring [55][56][57][58], little is still known regarding how the supplementation of the mother's diet with CLA affects progeny with cancer. Similarly, the impact of maternal diet during the fetal period on heart development has hardly been described.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that interactions between prenatal and postnatal exposure to an increased caloric supply are associated with permanent alterations in the hypothalamic neural networks involved in the regulation of satiety involving leptin . In this regard, changes in leptin sensitivity in the offspring are concomitant with increased adiposity associated with hyperinsulinemia and hypertriglyceridemia . Adipogenesis and adipose tissue mass increased mainly during lactation, which is an epigenetic modification from a high‐fat diet resulting in leptin gene induction in a depot‐specific manner .…”
Section: Discussionmentioning
confidence: 99%
“…40,48 In this regard, changes in leptin sensitivity in the offspring are concomitant with increased adiposity associated with hyperinsulinemia and hypertriglyceridemia. 3,49,50 Adipogenesis and adipose tissue mass increased mainly during lactation, which is an epigenetic modification from a high-fat diet resulting in leptin gene induction in a depotspecific manner. 51 The neonatal leptin surge, occurring from PND5 to PND13 in rodents, is critical for the correct development of the hypothalamic circuits involved in energy homeostasis and the expression of metabolic hormones.…”
Section: Effect Of the Maternal P Diet On Leptin Signaling In The Hmentioning
confidence: 99%